Effect of Seed Weight on Germination and Growth of Chir Pine (Pinus roxburghii Sargent) - Chauhan, P. S.; Raina, V. (Indian Forester, 1980)
Studies were carried out to find out the effect of seed weight on germination and growth of chir pine seedlings. Positive relationship have been found among seed weight and shoot length, root length, fresh weight of shoot and fresh weight of root in both the seed lots. There seems to be no relationship between the initial seed weight and germination percentage.